(untitled) (Interdisciplinary Studies Journal, 2025)
This article investigates the intersection between the thesis Humor and Interactivity: What Does WhatsApp Have to Do with It? (Siqueira, 2017) and the research developed by Anna Maria Moura for the documentary Aterro, Ancestral Technology (2023). The analysis highlights how digital communication and traditional cultural practices interconnect and complement each other, problematizing the relationship between innovation and ancestry. Based on the concept of the "interauthor subject," the study explores dynamics of interaction and authorship in cyberculture, contrasting them with folk communication and the preservation of local knowledge. The study demonstrates that new media do not replace, but rather reconfigure traditional communicative practices, fostering a dialogue between the global and the local. Furthermore, the research reveals how bricolage and improvisation (gambiarra), present in both audiovisual production and digital communication, function as strategies of cultural resistance and creative innovation.